Being While Doing: An Inductive Model of Mindfulness at Work - Lyddy, Christopher J.; Good, Darren J. (Frontiers in Psychology, 2017)
Mindfulness at work has drawn growing interest as empirical evidence increasingly supports its positive workplace impacts. Yet theory also suggests that mindfulness is a cognitive mode of “Being” that may be incompatible with the cognitive mode of “Doing” that undergirds workplace functioning. Therefore mindfulness at work has been theorized as “being while doing,” but little is known regarding how people experience these two modes in combination, nor how they interact. Drawing on a sample of 39 semi-structured interviews, this study explores how professionals experience being mindful at work. The relationship between Being and Doing modes demonstrated changing compatibility across individuals and experience, with two basic types of experiences and three types of transitions. We labeled experiences when informants were unable to activate Being mode while engaging Doing mode as Entanglement, and those when informants reported simultaneous co-activation of Being and Doing modes as Disentanglement. This combination was valuable for offsetting important limitations of the typical reliance on the Doing cognitive mode. Overall our results have yielded a comprehensive model of mindfulness at work, with the core experience, outcomes, and antecedent factors unified into one system that may inform future research and practice.